Education Curriculum Strategies in Five Countries: A Library Research Study of Singapore, Finland, Japan, Indonesia, and the United States - Maysa Thahira; Putri Nabila Sakinah; Ratu Zahra; Salsabila Ramadhani; Marhamah Marhamah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines curriculum strategies implemented in five countries Singapore, Finland, Japan, Indonesia, and the United States using a library research approach. The main objective of this research is to analyze similarities, differences, challenges, and strategic orientations in curriculum development across diverse national education systems. Data were collected from scholarly journal articles, government policy documents, and international education reports published by reputable institutions. The analysis indicates that each country adopts distinct curriculum strategies influenced by its socio-cultural context, governance structure, policy priorities, and long-term educational goals. Singapore emphasizes competency-based learning aligned with economic needs, Finland prioritizes flexibility and teacher autonomy, Japan focuses on character education and cultural values, Indonesia continues to adapt its curriculum to improve relevance and equity, while the United States highlights standards-based accountability and innovation. Despite these differences, common patterns emerge, particularly in the emphasis on competency development, integration of 21st-century skills, teacher quality improvement, and curriculum adaptability to global challenges such as digitalization and workforce transformation. The findings suggest that effective curriculum development requires a balance between global educational trends and local contextual needs. This study contributes to comparative education discourse by providing insights that may inform policymakers and educators in designing responsive and sustainable curriculum strategies.